2002
DOI: 10.1080/08958370290084827
|View full text |Cite
|
Sign up to set email alerts
|

Toxicologic Evaluation of Humectants Added to Cigarette Tobacco: 13-Week Smoke Inhalation Study of Glycerin and Propylene Glycol in Fischer 344 Rats

Abstract: Glycerin (CAS no. 56-81-5) and propylene glycol (CAS no. 57-55-6) are commonly used as humectant ingredients in manufactured cigarettes to control and maintain the moisture content of the cut tobacco filler. The potential of these added humectants to affect the toxicity of cigarette smoke was investigated in a subchronic nose-only smoke inhalation study in rats. Filtered test cigarettes were prepared from an American-style tobacco blend containing either glycerin added at 5.1% w/w tobacco, propylene glycol at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 18 publications
3
19
0
2
Order By: Relevance
“…An increase of mainstream smoke toxicity due to the use of 1,2-propylene glycol was not seen. Examining the effects of the humectants, glycerol and 1,2-propylene glycol added to tobacco, on mainstream cigarette smoke in a subchronic 13-week nose-only inhalation study with rats (described above in more detail), HECK et al (397) found no significant difference between the animal groups exposed to smoke from cigarettes with and without added humectants. Comparable results were obtained by BAKER et al (239) in their evaluation of the effects of tobacco additives on cigarette mainstream smoke toxicity using test cigarettes containing up to 8.3% 1,2-propylene glycol applied on tobacco in a casing mixture.…”
Section: 2-propylene Glycolmentioning
confidence: 99%
See 3 more Smart Citations
“…An increase of mainstream smoke toxicity due to the use of 1,2-propylene glycol was not seen. Examining the effects of the humectants, glycerol and 1,2-propylene glycol added to tobacco, on mainstream cigarette smoke in a subchronic 13-week nose-only inhalation study with rats (described above in more detail), HECK et al (397) found no significant difference between the animal groups exposed to smoke from cigarettes with and without added humectants. Comparable results were obtained by BAKER et al (239) in their evaluation of the effects of tobacco additives on cigarette mainstream smoke toxicity using test cigarettes containing up to 8.3% 1,2-propylene glycol applied on tobacco in a casing mixture.…”
Section: 2-propylene Glycolmentioning
confidence: 99%
“…HECK et al (397) examined cigarettes spiked with glycerol and 1,2-propylene glycol (singly and in combination) and found that the addition of these humectants to cigarettes did not significantly affect the biological activity of inhaled cigarette smoke in rats. GAWORSKI et al (406), in the study mentioned before, subjected the smoke of test cigarettes with target levels of 4, 7 and 10% 1,2-propylene glycol added to tobacco to chemical analysis (41 analytes), toxicological in vitro assays (bacterial mutagenicity and cytotoxicity using neutral red uptake) and a sub-chronic inhalation study.…”
Section: 2-propylene Glycolmentioning
confidence: 99%
See 2 more Smart Citations
“…Nr-COH; neutral red uptake cytoxicity assay with COH cells; SCE-COH: sister chromatid exchange assay in Chinese hamster ovary cells. Table 2 shows that the impact of tobacco additives on cigarette mainstream smoke toxicity was investigated through in vitro mutagenicity (Ames test) and mammalian cytotoxicity (Neutral red uptake) assays 29,30,31 , and in vivo sub-chronic (90 day) inhalation toxicity studies with rats 31,32,33,34 . In addition to these investigations (Table 2), a sub-chronic toxicity (26-week) study tested smoke condensates from cigarettes with and without tobacco additives for tumor promoting activity in the two-stage carcinogenicity test on mouse back skin 35 .…”
Section: S46mentioning
confidence: 99%